SOSIALISASI CO DIGESTION LIMBAH CAIR TAHU DAN KOTORAN SAPI DI CV PANDAWA FARM - Leila Kalsum; Rusdianasari; Aida Syarif; Yordan Hasan (Politeknik Negeri Sriwijaya, 2024)
This service activity provides benefits to CV Pandawa Farm, because it uses cow dung into environmentally friendly fuel energy. Sarnubi CV Pandawa Farm's Cattle Farm is a cattle farm that has been established for more than 10 years. more than 30 individuals. The location of this farm is in the Sukawinatan area which is not far from the Palembang City Waste Landfill. The environmental conditions of this farm are not good because health management of cow dung has not been implemented here. Processing cow dung into biogas can have a good impact on the environment because it maintains environmental cleanliness. Apart from that, biogas can be used to replace fossil fuels. CV Pandawa Farm does not yet understand how to process cow dung into biogas. In this socialization, counseling was provided by providing knowledge and understanding of how to process cow dung waste combined with tofu industry waste into biogas using a Fixed Dome Digester